2010
DOI: 10.1039/c0jm02011g
|View full text |Cite
|
Sign up to set email alerts
|

Composition and the thermoelectric performance of β-Zn4Sb3

Abstract: b-Zn 4 Sb 3 is a promising thermoelectric material due to the abundance of zinc and antimony and reports of high efficiency in bulk samples. This work establishes the high temperature properties of b-Zn 4 Sb 3 across the phase stability window. By controlling the stoichiometry, the Hall carrier concentration can be tuned from 6-9 Â 10 19 cm À3 without requiring extrinsic dopants. The trend in Seebeck coefficient on carrier concentration is rationalized with a single, parabolic band model. Extremely low lattice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
105
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 37 publications
7
105
0
Order By: Relevance
“…Studies of ZnSb have been limited by its high thermal conductivity. 64,65 However, our facile, low-temperature solution-phase synthesis could be useful as a means of mitigating this problem, as it allows for reduction in grain size or nanostructuring. 13,[66][67][68][69] Characterization of LiZnSb using solid state NMR.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of ZnSb have been limited by its high thermal conductivity. 64,65 However, our facile, low-temperature solution-phase synthesis could be useful as a means of mitigating this problem, as it allows for reduction in grain size or nanostructuring. 13,[66][67][68][69] Characterization of LiZnSb using solid state NMR.…”
Section: Resultsmentioning
confidence: 99%
“…In the superionic phase, cations exhibit liquid-like diffusivity [3,4] and this disordered nature typically results in a very low lattice thermal conductivity (<1 W m −1 K −1 ). Many of the superionic compounds, particularly those that are also good electric conductors, indeed show promising thermoelectric properties as exemplified by Cu 2 Se [1,5], Cu 2 S [6,7], Ag 2 Se [8,9], and Zn 4 Sb 3 [10]. Cation movement is seen to be suppressed with the addition of lithium.…”
mentioning
confidence: 87%
“…16 and 18) and YbCd 2Àx Zn x Sb 2 , both of which have zT values above unity at high temperatures. 11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Recently, Yb 9 Mn 4.2 Sb 9 was shown to have promising thermoelectric performance (zT ¼ 0.7 at 950 K) by Bux et al 17 The structure of Yb 9 M 4+x Sb 9 is shown in Fig. 1, where M can be Fig.…”
Section: Introductionmentioning
confidence: 99%